Motivasi dalam mengikuti kegiatan ekstrakurikuler bolatangan untuk siswa SMA/SMK/MA di Kabupaten Demak 2020 (Universitas Negeri Semarang, 2022)
Demak Regency has consistent achievements in the sport of handball, this can not be separated from the handball extracurricular activities held by SMA/SMK/MA in Demak Regency. Therefore, the aim of this researcher is to understand how high the motivation is in participating in extracurricular handball activities for SMA/SMK/MA students in Demak Regency 2020. The approach used is descriptive qualitative. The locations and areas studied were SMAN 3 Demak, SMKN 1 Demak, SMKN 2 Demak, SMAN 1 Karangtengah, MA Al-Anwar, SMK Nusa Bangsa. The results of this study are the motivation in participating in handball extracurricular activities for high school / vocational / MA students in Demak Regency 2020, it is known that students' intrinsic motivation in participating in handball extracurricular activities in Demak Regency is in the high category with a percentage of 56.36%. Each indicator in the intrinsic factor, the indicator gets the highest percentage with a percentage reaching 43.64%. Then for the extrinsic motivation of students in participating in handball extracurricular activities in Demak Regency, it is included in the high category with a percentage of 38.18%. Each indicator in the intrinsic motivation factor, the community indicator gets the highest percentage with a percentage reaching 47.28%.